Kingdom-wide analysis of the evolution of the plant type III polyketide synthase superfamily. Issue 3 (30th December 2020) - Naake, Thomas; Maeda, Hiroshi A; Proost, Sebastian; Tohge, Takayuki; Fernie, Alisdair R
Abstract: The emergence of type III polyketide synthases (PKSs) was a prerequisite for the conquest of land by the green lineage. Within the PKS superfamily, chalcone synthases (CHSs) provide the entry point reaction to the flavonoid pathway, while LESS ADHESIVE POLLEN 5 and 6 (LAP5/6) provide constituents of the outer exine pollen wall. To study the deep evolutionary history of this key family, we conducted phylogenomic synteny network and phylogenetic analyses of whole-genome data from 126 species spanning the green lineage including Arabidopsis thaliana, tomato ( Solanum lycopersicum ), and maize ( Zea mays ). This study thereby combined study of genomic location and context with changes in gene sequences. We found that the two major clades, CHS and LAP5/6 homologs, evolved early by a segmental duplication event prior to the divergence of Bryophytes and Tracheophytes. We propose that the macroevolution of the type III PKS superfamily is governed by whole-genome duplications and triplications. The combined phylogenetic and synteny analyses in this study provide insights into changes in the genomic location and context that are retained for a longer time scale with more recent functional divergence captured by gene sequence alterations. Abstract : Phylogenetic and syntenic analyses of whole genome data reveal that macroevolution of the type III polyketide synthase superfamily is mainly governed by whole-genome duplications and triplications.